Detection of dengue virus type 2 of Indian origin in acute febrile patients in rural Kenya. - Moses Muia Masika; Essi M Korhonen; Teemu Smura; Ruut Uusitalo; Katariina Vapalahti; Dufton Mwaengo; Anne J Jääskeläinen; Omu Anzala; Olli Vapalahti; Eili Huhtamo (Public Library of Science (PLoS), 2020)
Dengue virus (DENV) has caused recent outbreaks in coastal cities of Kenya, but the epidemiological situation in other areas of Kenya is largely unknown. We investigated the role of DENV infection as a cause of acute febrile disease in non-epidemic settings in rural and urban study areas in Kenya. Altogether, 560 patients were sampled in 2016-2017 in rural Taita-Taveta County (n = 327) and urban slums of Kibera, Nairobi (n = 233). The samples were studied for DENV IgM, IgG, NS1 antigen and flaviviral RNA. IgG seroprevalence was found to be higher in Taita-Taveta (14%) than in Nairobi (3%). Five Taita-Taveta patients were positive for flaviviral RNA, all identified as DENV-2, cosmopolitan genotype. Local transmission in Taita-Taveta was suspected in a patient without travel history. The sequence analysis suggested that DENV-2 strains circulating in coastal and southern Kenya likely arose from a single introduction from India. The molecular clock analyses dated the most recent ancestor to the Kenyan strains a year before the large 2013 outbreak in Mombasa. After this, the virus has been detected in Kilifi in 2014, from our patients in Taita-Taveta in 2016, and in an outbreak in Malindi in 2017. The results highlight that silent transmission occurs between epidemics and also affects rural areas. More information is needed to understand the local epidemiological characteristics and future risks of dengue in Kenya.